2011
DOI: 10.1590/s0004-27302011000500002
|View full text |Cite
|
Sign up to set email alerts
|

Regulação do metabolismo de glicose e ácido graxo no músculo esquelético durante exercício físico

Abstract: SUMMARYThe glucose-fatty acid cycle explains the preference for fatty acid during moderate and long duration physical exercise. In contrast, there is a high glucose availability and oxidation rate in response to intense physical exercise. The reactive oxygen species (ROS) production during physical exercise suggests that the redox balance is important to regulate of lipids/carbohydrate metabolism. ROS reduces the activity of the Krebs cycle, and increases the activity of mitochondrial uncoupling proteins. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
9
0
5
Order By: Relevance
“…In addition, a study in mice with high muscle expression of SOD revealed that these animals exhibited a higher rate of glucose uptake during muscle contraction compared to the control group (Schrauwen et al 2003). These results support the proposition that ROS significantly affect the regulation of glucose metabolism during intense muscular activity (Silveira et al 2011).…”
Section: Discussionsupporting
confidence: 72%
“…In addition, a study in mice with high muscle expression of SOD revealed that these animals exhibited a higher rate of glucose uptake during muscle contraction compared to the control group (Schrauwen et al 2003). These results support the proposition that ROS significantly affect the regulation of glucose metabolism during intense muscular activity (Silveira et al 2011).…”
Section: Discussionsupporting
confidence: 72%
“…During moderate exercise maintained for a long period, fatty acids are mobilized from adipose tissue (peripheral and intramuscular) through lipolysis and are used by skeletal muscle. In contrast, during high-intensity exercise, The release of fatty acids from adipose tissue is markedly decreased, followed by an increase in glucose availability and oxidation [59]. In group 6, The horse breed studied is The racing line of The Quarter Horse, a breed used for shorter distance races, which are classified as high-intensity exercise.…”
Section: Gene-biological Process Networkmentioning
confidence: 99%
“…Favaro e Vidotti (2010) analisaram a resposta glicêmica durante uma sessão de RPM® em praticantes de ciclismo indoor do gênero feminino, e verificaram que houve uma diminuição do valor glicêmico após o primeiro estímulo de alta intensidade, no qual se aproxima do protocolo e resultados utilizados neste estudo. Silveira et al (2011) explica que em exercícios de alta intensidade há uma maior degradação de glicose, sendo este aumento de sete a 20 vezes mais em comparação aos níveis de repouso (AFONSO et al, 2003) v.3, n.17, p.456-462, 2009.…”
Section: Instrumentos E Procedimentosunclassified